2015
DOI: 10.1002/asia.201500048
|View full text |Cite
|
Sign up to set email alerts
|

A General Direct Arylation of Polyfluoroarenes with Heteroaryl and Aryl Chlorides Catalyzed by Palladium Indolylphosphine Complexes

Abstract: The first general examples of direct coupling of heteroaryl chlorides, especially substituted 2-pyridyl chlorides which were previously found to be problematic, with electron-deficient polyfluoroarenes are reported. Pd(OAc)2 associated with 3-(dicyclohexylphosphino)-2-phenylindole L1 serves as the effective catalyst which allows the challenging direct coupling of heteroaryl chlorides and polyfluoroarenes. In addition to heterocycles, a wide range of non-activated and activated aryl chlorides and alkenyl chlori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Recently, Walsh showed that indolyl-backbone phosphines were effective in promoting Pd-catalyzed monoarylation of α-acidic C–H bonds . It is to our persisting and great interest to use indolylphosphines in Pd-catalyzed cross couplings and direct arylation of acidic C–H bonds . Herein, we demonstrate and report the rational design of a new indolylphosphine ligand to address the challenges that arose from the Pd-catalyzed mono-α-arylation of acetone with aryl chlorides.…”
mentioning
confidence: 99%
“…Recently, Walsh showed that indolyl-backbone phosphines were effective in promoting Pd-catalyzed monoarylation of α-acidic C–H bonds . It is to our persisting and great interest to use indolylphosphines in Pd-catalyzed cross couplings and direct arylation of acidic C–H bonds . Herein, we demonstrate and report the rational design of a new indolylphosphine ligand to address the challenges that arose from the Pd-catalyzed mono-α-arylation of acetone with aryl chlorides.…”
mentioning
confidence: 99%
“…Further screening on the solvent revealed that both 2-MeTHF and EtOAc resulted in higher product yield (entries 10-14). Encouragingly, a combination of 2-MeTHF and EtOAc in 1 : 1 ratio showed the best product yield whereas further altering the ratio to 1 : 3 or 3 : 1 did not give significant effect on the reaction efficiency (entries [15][16][17]. The best Pd/ ligand ratio was found to be 1 : 2.5 (entries 10 vs 18-20).…”
Section: Resultsmentioning
confidence: 98%
“…[16] Our group also presented a Pd/PCy-Phendole-phos catalyst system for the olefination of pentafluorobenzene using 1-chlorocyclopent-1-ene. [17] The cross-coupling between 4-chlorocoumarin and polyfluoroarenes was disclosed by Wang using Pd(OAc) 2 /SPhos catalyst system. [18] A CuI/phen catalyst system was probed by Daugulis to show one record example of coupling of pentafluorobenzene and βbromostyrene to give 77 % E-isomer and 12 % Z-isomer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Growing efforts has been paid to develop the attractive method. New catalyst systems such as cyclopalladated ferrocenylimine complex [36, 37] and palladium-indolylphosphine complex [23, 38, 39] were reported successively. In 2007, the first example of borylation/cross-coupling protocol from aryl chlorides was reported [28].…”
Section: Introductionmentioning
confidence: 99%